2020
DOI: 10.3389/fmicb.2020.01945
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Processes and Microbial Communities in the Water Column of the Polar Meromictic Lake Bol’shie Khruslomeny at the White Sea Coast

Abstract: Microbiological, molecular ecological, biogeochemical, and isotope geochemical research was carried out at the polar Lake Bol'shie Khruslomeny at the coast of the Kandalaksha Bay, White Sea in March and September 2017. The uppermost mixolimnion was oxic, with low salinity (3-5%). The lower chemocline layer was browngreen colored, with very high content of particulate organic matter (up to 11.8 mg C L −1). The lowermost monimolimnion had marine salinity (22-24%) and very high concentrations of sulfide (up to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…All plates were incubated in the dark at room temperature for 21 days, which was shown to reach the stable growth phase according to our pre-experiment. After 21 days, cell counting was used to screen the wells for positive growth defined as a minimum of 1 × 10 6 cells/mL (the ubiquitous density observed in aquatic environment) [ 20 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…All plates were incubated in the dark at room temperature for 21 days, which was shown to reach the stable growth phase according to our pre-experiment. After 21 days, cell counting was used to screen the wells for positive growth defined as a minimum of 1 × 10 6 cells/mL (the ubiquitous density observed in aquatic environment) [ 20 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lake Bol'shie Khruslomeny, with a maximum depth of approximately 18 m, is the largest known lake separated from the Kandalaksha Gulf [29]. Unlike other lakes under study, Lake Bol'shie Khruslomeny was artificially separated from the sea.…”
Section: Study Areamentioning
confidence: 99%
“…Consequently, a meromictic structure emerged in this lake. Beneath the halocline, situated at a depth of 2-3 m, a sulfide water mass developed around 4-4.5 m deep [29].…”
Section: Study Areamentioning
confidence: 99%
“…in Lake Shunet [6, 7] and Thiocapsa marina in Lake Trekhtsvetnoe [10]. Many studies have suggested that PSBs play an important role in the cycling of various nutrients, including carbon, nitrogen and sulfur, specifically at the oxic–anoxic interface of stratified lakes [9, 11–19]; however, the ecological role of PSBs in Lake Shunet remains unclear.…”
Section: Introductionmentioning
confidence: 99%